Impact assessment of a marine and coastal protected area on fishing households through a counterfactual approach. A Senegalese case study (West Africa). (1st April 2018) - Weigel, Jean Yves; Morand, Pierre; Charpin, Agnès; Sadio, Oumar
Abstract: The setting up of marine and coastal protected areas, one of most significant strategies of coastal management employed worldwide to maintain ecosystem services and mitigate biodiversity loss, has to be accompanied by an impact evaluation to guide decision-makers, practitioners and the relevant population. This paper presents a counterfactual approach of fishing households' profitability and vulnerability after the setting up of a marine and coastal protected area (MPA). By using the DID method (Difference-in-Differences), this approach is a comparison of average change in outcome over time for the treated group (fishing households with a main fishing ground adjacent to the MPA) and for the control group (fishing households with a main fishing ground remote from the MPA). From a dataset made up of 183 fishing households in Betenti Islands (Saloum, Delta, Senegal) surveyed twice (one year before the MPA's setting up and six years after it) and divided in two geographical strata, the main result is the applicability and confirmation of the value of a counterfactual approach to assess the positive effect of proximity with a MPA on fishing households' income and vulnerability, independently of fishing productive assets and conditions, and of any change that have affected them during the period taken in consideration. This counterfactual assessment should help to calibrate the necessary investments and to adapt the functioning of a MPA but also to target adequate mitigation and compensation measures for the non-beneficiary households. Highlights: A counterfactual approach to assess the impact of a marine and coastal protected area on the fishing households' profitability and vulnerability. A test of the applicability of the Difference-In-Differences method to estimate the effect of a marine and coastal protected area based on a West African case study. The necessary conditions: similarity in the fishing activities, large sample size and demanding data collection design, a multidisciplinary dimension.